Interactions among variants in P53 apoptotic pathway genes are associated with neurologic deterioration and functional outcome after acute ischemic stroke. Issue 5 (7th January 2020) - Yi, Xingyang; Zhou, Qiang; Sui, Guo; Ren, Gaoping; Tan, Lili; Li, Jie; Lin, Jing; Bao, Shaozhi
Abstract: Objective: Neurologic deterioration (ND) and functional outcome after ischemic stroke (IS) are not accurately predicted by clinical pictures on admission. The aim of present study was to investigate the association of variants in P53 apoptotic pathway genes with ND and functional outcome after IS. Methods: Genotypes of nine variants in apoptosis‐relevant genes were measured in patients with acute IS. Gene–gene interactions were analyzed by generalized multifactor dimensionality reduction (GMDR). The primary outcome was ND. ND was diagnosed in patients who worsened ≥2 points (National Institutes of Health Stroke Scale [NIHSS] score) within the first 10 days of stroke onset. The secondary outcome was functional status at 90 days after IS as measured by modified Rankin Scale (mRS) score. Results: A total of 705 enrolled patients, ND occurred in 174 (24.7%) patients, and 184 (26.1%) patients were poor functional outcome (mRS score > 2). Although the nine variants were not significantly associated with ND and functional outcome by univariate analysis, there was a gene–gene interaction among P53 rs1042522, MDM‐2 rs2279744, and MMP‐9 rs3918242 using GMDR analysis. The high‐risk interaction among the three variants was independently associated with higher risk of ND (HR, 2.04, 95% CI: 1.22–5.64, p = .018) and poor functional outcome (OR, 2.68, 95% CI: 1.68–7.86, p = .004) after adjusting for the covariates. Conclusion: The interactions among P53 rs1042522, MDM‐2 rs2279744, and MMP‐9 rs3918242 may increase the risk of ND and poor functional outcome and may be considered as a genetic marker of predicting ND and poor functional outcome after stroke. Abstract : (a) The neurologic deterioration (ND) and functional outcome after ischemic stroke (IS) are not accurately predicted by clinical pictures on admission. (b) There was a gene–gene interaction among P53 rs1042522, MDM-2 rs2279744, and MMP-9 rs3918242 using GMDR analysis. (c) The interactions among P53 rs1042522, MDM-2 rs2279744, and MMP-9 rs3918242 may increase the risk of ND and poor functional outcome and may be considered as a genetic marker predicting ND and poor functional outcome after stroke.